2017
DOI: 10.4103/ijo.ijo_233_17
|View full text |Cite
|
Sign up to set email alerts
|

Altered tear inflammatory profile in Indian keratoconus patients - The 2015 Col Rangachari Award paper

Abstract: Purpose:Conventionally, keratoconus (KC) has been considered a noninflammatory corneal ectatic disorder. Recent evidence suggests a possible role of inflammation in the pathogenesis of KC. Hence, we analyzed the levels of inflammatory factors in the tear fluid of Indian KC patients.Methods:Tear fluid samples were collected from age- and sex-matched healthy controls and KC patients (with different grades). The levels of the inflammatory factors in tears were analyzed using cytometric bead array (Human Soluble P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…IL-1β, IL-6, IL-17A, TNFα, IFNγ, IgE, MMP2, EPO, PDGF-BB, sVCAM, sL-selectin, granzyme-B and perforin were observed to be significantly increased compared to controls in two or more of KC grades. This finding is consistent with earlier observations reporting increased levels of IL-1β 26 , 40 42 , IL-6 24 , 26 , 30 , TNFα 41 , IL-17A 40 , 43 , IFNγ 44 and MMP2 26 in the tear fluid of KC patients. The observed variation in tear fluid expression of MMP9 24 33 , 45 , IL-8 26 , 33 , 46 , IL-13 40 , IL-21 40 , IL-23 40 , IFNα 40 , MCP1 40 and CCL5 31 , 32 , 44 between the current study and previous reports, may be attributed to differences in sample size and stage of KC investigated in the cohort.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…IL-1β, IL-6, IL-17A, TNFα, IFNγ, IgE, MMP2, EPO, PDGF-BB, sVCAM, sL-selectin, granzyme-B and perforin were observed to be significantly increased compared to controls in two or more of KC grades. This finding is consistent with earlier observations reporting increased levels of IL-1β 26 , 40 42 , IL-6 24 , 26 , 30 , TNFα 41 , IL-17A 40 , 43 , IFNγ 44 and MMP2 26 in the tear fluid of KC patients. The observed variation in tear fluid expression of MMP9 24 33 , 45 , IL-8 26 , 33 , 46 , IL-13 40 , IL-21 40 , IL-23 40 , IFNα 40 , MCP1 40 and CCL5 31 , 32 , 44 between the current study and previous reports, may be attributed to differences in sample size and stage of KC investigated in the cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, IL-6 54 , IL-17A 55 , TNFα 56 and IFNγ 57 , 58 induce the expression of MMPs and inhibit the production of collagen in various cells and tissues. The levels of TGFβ1, a potent pro-fibrotic factor, were higher in tear fluid of KC patients 40 , however, the current study observed a significant increase in TGFβ1 only in the highest grade of KC. This finding is in line with fibrotic changes observed in advanced KC.…”
Section: Discussioncontrasting
confidence: 92%
“…Tear fluid was collected using Schirmer's strip and capillary tubes as described earlier. [1112] Schirmer's strip-based tear fluid collection was followed as it was reported to be suitable and comparable with capillary tube-based tear fluid collection for downstream analysis. [13] Briefly, tear fluid from the subjects was collected using sterile Schirmer's strips (5 × 35 mm 2 ; Tear Strips, Contacare Opthalmics and Diagnostics, India) according to the Schirmer's test I procedure.…”
Section: Methodsmentioning
confidence: 99%
“…[89] Tear fluid can be easily obtained using well-established methods of collection through Schirmer's strips and capillary tubes. [101112] Moreover, tears are a non-invasive source of sampling as opposed to blood collection for plasma, which could improve donor compliance during sampling, particularly for longitudinal follow-up monitoring and in pediatric subjects. Thus, optimizing an ELISA-based method for the detection of dopamine from tear fluid would serve as an additional tool for monitoring local dopamine status.…”
mentioning
confidence: 99%
“…Despite these contradictions, inflammatory theory has been widely investigated. In a paper published in this issue,[ 2 ] investigators from Narayana Nethralaya evaluated levels of different inflammatory markers in tear film in patients with keratoconus and compared these with those in otherwise healthy individuals with no evidence of keratoconus or other inflammatory diseases. The authors hypothesized that altered collagen structure and consequent biomechanical weakening as well as deregulated epithelial and stromal proteins demonstrated in KC could be because of inflammation.…”
mentioning
confidence: 99%